Respuesta :

Given :-

  • a² - 2a - b² = 0
  • 2b + 2ab = 0

To find :-

  • Value of a and b .

Solution :-

Taking second equation:-

  • 2b + 2ab = 0
  • 2b ( 1 + a ) = 0
  • 2b = 0 or (1+a) = 0
  • b = 0 , a = -1

Substitute in first equation :-

  • a² - 2a - b² = 0

When b = 0 ,

  • a² - 2a - 0² = 0
  • a² - a = 0
  • a( a -1) =0
  • a = 0 , 1

When a = -1 ,

  • (-1)² - 2*(-1) - b² = 0
  • 1 + 2 - b² = 0
  • b² = 3
  • b = ±√3

Answer :-

  • a = 0,1 ; b = 0
  • a = -1 , b = ±√3
ACCESS MORE